An environment for processing compound media streams : work in progress paper V 2.0 - Björn Feustel; Andreas Kárpáti; Torsten Rack; Thomas C. Schmidt (International Conference of European University Information Systems 2001, 2001)
With today s widespread availability of networked multimedia potentials embedded in an infrastructure of qualitative superior kind the distribution of professionally styled multimedia streams has fallen in the realm of possibility. This paper presents a prototypic environment - both model and runtime system - for processing composite media streams variably composed of multimedia data objects. The system consists of an intelligent media database, a Web-authoring tool, a time directed presentation stream and is based on a hypermedia data model of reusable object components. The plug-in free runtime system is designed as a pure JAVA implementation. Further educational applications of our architecture are presented, as well.
Keywords: Synchronized Media; Hypermedia Modelling; Multimedia Database; Web-Authoring